Contrastive Analysis Between English Medical Terms with Affixes and Their Indonesian Equivalent in Dorland’s Illustrated Medical Dictionary - Nur Indah Sulistyowati Lutfiyah; Jumanto Jumanto (CV. Rustam, 2023)
Medical terms are language units used to describe medical conditions such as diseases, symptoms, anatomy, and procedures. Medical terms are composed of a combination of affixes and root words. This research focused on contrastive analysis, a study comparing two languages, the source language and their equivalent in the target language. This study aims (1) to find out similarities between English medical terms with affixes in English and their Indonesian equivalents in Dorland's Illustrated Medical Dictionary (2) to find out differences between English medical terms with affixes in English and their Indonesian equivalents in Dorland's Illustrated Medical Dictionary (3) to predict learning problems based on the differences between English medical terms with affixes in English and their Indonesian equivalents in Dorland's Illustrated Medical Dictionary. The data source of this research is